Context residual energy-based trust management in mobile ad hoc networks. (2017) - Vijayan, R.; Jeyanthi, N.
The rapid growth of network communications also discloses the problem of vulnerability to various third-party attacks. MANETs being unpredictable with its infrastructure and topology, it is prone to various attacks easily. Trust plays a pivotal role in the MANETs in predicting the trust values dynamically based on the particular situation or context of a node. In this paper we propose a context residual energy-based trust management in mobile ad hoc networks (CEBTM) by sharing the context data onto the other nodes in the network would give a better solution to this problem. We considered much context data like residual energy and packet drop strategy of the nodes are considered. An agent helps in retrieving the two context data from the neighbour nodes. Using this datum, the weight and reputation-based trust in each node with respect to the context data are found and is then fed into the fuzzy filter for analysis. This feature would help to understand whether the computed trust value is trustworthy or not. If not, a negative alarm is generated and sent to the other nodes for revocation. The proposed system is simulated in the ns-2 environment.